Machinery from Brazilian Wooden Housing Production: Size and Overall Obsolescence - De Araujo, Victor A.; Lima, Mauri P. de [UNESP]; Biazzon, Joao C. [UNESP]; Vasconcelos, Juliano S. [UNESP]; Munis, Rafaele A. [UNESP]; Morales, Elen A. M. [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Nogueira, Claudia L.; Savi, Antonio F. [UNESP]; Severo, Elias Taylor D. [UNESP]; Christoforo, Andre L.; Sorrentino, Marcos; et al. (North Carolina State Univ Dept Wood & Paper Sci, 2018)
In the current competitive market, production efficiency and product quality are prioritized by the whole industry. Machinery characterization is an understudied topic, particularly in those sectors focused on basic raw material production, processing, and/or heavy industrialization. For this reason, the wooden housing sector requires evaluation to identify its mechanical potential and support future policies dealing with industrial development. This study aimed to identify the equipment and machinery from Brazilian timber housing producers. Such a sectoral study involved individual personal data collection by way of face-to-face interviews. Sampled producers were asked about equipment/machinery size, drying process availability, and the range of overall obsolescence from these devices. Thus, tools, portable machines, and medium-sized machinery exhibited the highest popularities, revealing a lower industrial level. Most of these producers do not have machined drying processes because of the demand for static infrastructures. The low obsolescence was a result of the greater utilization of compact equipment, which is easier to replace because of its low cost. Lower-cost machinery could also stimulate in the creation of new businesses for this sector.
Keywords: Machine; Equipment; Wooden construction; Sectoral research; Personal interview